The Mother Archetype in the Drama “The Sanctuary of Abraham” by Mavro Vetranović - Jekić, Sara R. (Collection of Papers of the Faculty of Philosophy in Priština, 2024)
Vetranović’s work, diverse in genres and themes, marked the 16th century and introduced the Christian Renaissance as a new ruling epoch in Dubrovnik, with him being a key representative. With his creative skills, this Benedictine monk, poet, devotee, and restorer of Christian themes and motifs in literature “revived” striking biblical female characters, who even then served an important function – to provide a universal model of education and governance for the female population. Inspired by the Old Testament biblical story (from the Book of Genesis) about Abraham’s testing and the most difficult sacrifice for any parent, Vetranović wrote the pious drama The Sanctuary of Abraham, in which he paid special attention to Abraham’s wife, Sarah. Sarah enchanted the then-reading audience with her spiritual beauty and moral sublimity, while her sacrifice for her only son and perseverance in faith, love, and hope established her as a good example of the archetype of unconditional maternal love.